Investing for Impact: A Case Study of Academic Institutions of District Jalandhar (Punjab) - Kaur, Amandeep; Singh, Jagjit (DESIDOC Journal of Library & Information Technology, 2016)
The present article focuses on the impact of new technology on the library services. The basic theme is based on the use of technology in the academic institutes. The article also highlights the major points like impact of automation/technology on print sources, staff, infrastructure, space, etc. The data collected shows the impact on services like reference and xeroxing. As the change demands lots of funds, so the data is collected to know the impact of technology on various sections of the library. The article also highlights the role of authority/management to generate sources and services. The article concluded that the change should be accepted due to the positive updates shown in the library.